TBLT STRATEGIES ON 7th GRADERS’ SPEAKING ACHIEVEMENT: STUDENTS’ VIEW - Aprillia Putri Aqila; Vivin Triwulan Rahayu; Eliasanti Agustina (Universitas Wiralodra, 2026)
This study aimed to explore students' perceptions of the implementation of Task-Based Language Teaching (TBLT) in improving English speaking skills among 7th-grade students. Conducted at SMPN 34 Surabaya during the 2024/2025 academic year, this qualitative research employed a case study to understand students' lived experiences. 3 participants from VII-H were selected purposively. The data were analyzed using six steps of thematic analysis. Additionally, the instrument was validated through experts, and the data were validated using member checking. The findings revealed that students perceived TBLT as an engaging and effective method that enhanced their fluency, vocabulary acquisition, and confidence in speaking English. They appreciated real-world tasks such as role plays and peer interviews, which provided meaningful practice and reduced anxiety. Collaborative learning and teacher support played a vital role in building a supportive environment. However, challenges such as limited vocabulary recall and speaking anxiety were still present. Students suggested incorporating more varied tasks, multimedia resources, and preparation time before speaking activities to improve the learning experience. This study established that TBLT had significant potential to engage students and enhance their confidence in speaking English when it was implemented conscientiously.